Perancangan Aplikasi Media Sosial “PANAMA” Sebagai Platform Kreatif: Pendekatan Inofatif Dalam Meningkatkan Keterlibatan Pengguna Melalui Fitur Android Multimedia - Annisa Yola Syafitri; Sularno; Nori Sahrun (Journal Of Informatics And Busisnes, 2023)
This research aims to design a creative social media application called "PANAMA" with an innovative approach to enhance user engagement through Android multimedia features. PANAMA is designed as a social media application that provides interactive and creative experiences for users to share multimedia content. In the design of this application, an innovative approach is employed by integrating comprehensive Android multimedia features, such as adding posts, profile pictures, and image editing. These features enable users to upload, edit, and share multimedia content directly through the PANAMA application. Additionally, PANAMA also offers social features such as commenting, liking, and content sharing with other users. These features are designed to enhance user interaction and engagement within the PANAMA community. The application is expected to provide an engaging and interactive experience for users in sharing multimedia content. Users are encouraged to increase their engagement within the PANAMA community through the creative and innovative features offered by the application.